The ascending aorta of male hypertensive bicuspid aortic valve patients preferentially associated with a cellular aneurysmal phenotype. Issue 8 (19th April 2022) - Bergeron, Alexandre; Hertig, Vanessa; Villeneuve, Louis; Chauvette, Vincent; El‐Hamamsy, Ismail; Calderone, Angelino
Abstract: Male sex and hypertension represent risk factors in the progression of an aortic aneurysm. The present study examined the morphological/cellular phenotype of the ascending aorta (AA) of male and female patients diagnosed with a bicuspid aortic valve (BAV) to test the hypothesis that hypertension‐induced remodeling of male BAV patients preferentially recapitulated the expression of a panel of proteins favoring aneurysm formation. The diameter of the AA of hypertensive male (35 ± 6 mm) and female (39 ± 5 mm) BAV patients was comparable to normotensive patients reflecting an early phase of vessel expansion. Morphological/structural remodeling of the medial region of the AA of male normotensive and hypertensive BAV patients were comparable. Protein levels of non‐muscle myosin IIB, the cell cycle inhibitor p27kip1, tumor suppressor p53 and matrix metalloproteinase‐2 and −9 were significantly upregulated in the AA of male hypertensive BAV patients. In female hypertensive BAV patients, collagen content was significantly increased whereas elastin content and medial width of the AA were similar to normotensive BAV patients. In the AA of female hypertensive BAV patients, matrix metalloproteinase‐9 and p27kip1 protein levels were unchanged whereas p53 and matrix metalloproteinase‐2 protein expression was significantly reduced. Nestin protein levels were diminished in the AA of male and female hypertensive BAV patients. Thus, sexual dimorphic remodeling of the AA was prevalent in hypertensive BAV patients. Moreover, during the early phase of vessel expansion, the AA of male hypertensive BAV patients was preferentially associated with the upregulation of a panel of proteins linked to progressive dilatation and potential aneurysm formation. Abstract : Sexual dimorphic remodeling of the ascending aorta was prevalent in hypertensive bicuspid aortic valve patients and the cellular phenotype reported in male hypertensive patients preferentially recapitulated a pattern of expression favoring further vessel expansion and potential aneurysm formation.